The Waves of Time : Long-Term Change and International Relations. - Dark, K. R. (History and Politics in the 20th Century: Bloomsbury Academic., 2000)
"This volume provides an overview of the whole range of long-term analyses in international relations. It evaluates and draws on theoretical approaches in both the humanities and social sciences - in subjects such as sociology, history, anthropology and archaeology - and recent progress in evolutionary theory and the mathematical study of complexity. The resulting analysis reinterprets processes of global political change in the past and present, and opens fresh areas of enquiry for international relations."--Bloomsbury Publishing